Size distribution of bubbles in agitated viscous N ewtonian and non‐ N ewtonian solutions - Momiroski, Vinko; Bhattacharya, Sati; Davoody, Meysam; Abdul Raman, Abdul Aziz; Parthasarathy, Rajarathinam (Wiley, 2018)
The effects of impeller type, Newtonian shear thinning liquid viscosities, and noncoalescing conditions on the impeller gas cavities, impeller power consumption, and Sauter mean bubble diameter (d32) in a multiphase agitated vessel were systematically studied. An underwater recording technique was used to study gas cavities and bubble size in various operating and design conditions. The gas cavity images were used to relate d32 to gas cavity structure. It was observed that d32 values increase with an increase in Newtonian and shear thinning liquid viscosities. Results also indicate that impellers operating in shear thinning liquids consume higher gassed power at the same operating conditions compared with those in Newtonian fluids. In addition, the d32 values in noncoalescing liquids are substantially smaller compared with those in coalescing solutions at the same Pg/V. Mathematical correlations are proposed for estimating the d32 in the impeller discharge stream and Pg/V in viscous Newtonian and non-Newtonian solutions.